Treatment of chronic anterior shoulder dislocation by open reduction and simultaneous Bankart lesion repair - Rouhani Alireza; Navali Amirmohammad (BMC, 2010)
Abstract Background Untreated chronic shoulder dislocation eventually leads to functional disability and pain. Open reduction with different fixation methods have been introduced for most chronic shoulder dislocation. We hypothesized that open reduction and simultaneous Bankart lesion repair in chronic anterior shoulder dislocation obviates the need for joint fixation and leads to better results than previously reported methods. Methods Eight patients with chronic anterior dislocation of shoulder underwent open reduction and capsulolabral complex repair after an average delay of 10 weeks from injury. Early motion was allowed the day after surgery in the safe position and the clinical and radiographic results were analyzed at an average follow-up of one year. Results The average Rowe and Zarin's score was 86 points. Four out of eight shoulders were graded as excellent, three as good and one as fair (Rowe and Zarins system). All patients were able to perform their daily activities and they had either mild or no pain. Anterior active forward flexion loss averaged 18 degrees, external active rotation loss averaged 17.5 degrees and internal active rotation loss averaged 3 vertebral body levels. Mild degenerative joint changes were noted in one patient. Conclusion The results show that the overall prognosis for this method of operation is more favorable than the previously reported methods and we recommend concomitant open reduction and capsulolabral complex repair for the treatment of old anterior shoulder dislocation. Level of Evidence Therapeutic study, Level IV (case series [no, or historical, control group])